Pemanfaatan Sistem Informasi Pendidik dan Tenaga Kependidikan (SIMPATIKA) Sebagai Dasar Pengambilan Keputusan dan kebijakan di Kementerian Agama - Sri Damayanti; Dimas Ahmad Rizal (Lembaga Sosial Rumah Indonesia, 2021)
This research will discuss SIMPATIKA as a basis for decision making and policies in the Ministry of Religion Yogyakarta. SIMPATIKA has a role in supporting all government needs in capturing PTK data, as in the Education and Madrasah Sector (DIKMAD) Regional Office of the Ministry of Religion DIY maximally utilizes SIMPATIKA data as a means of decision making. This research is descriptive qualitative research. This study's population was the head of the field, the head of the Kasi, the staff/operator of SIMPATIKA Kanwil, 3 SIMPATIKA operators of the institution. Sampling is based on 3M's criteria of knowing, understanding, and experiencing by using data collection techniques, namely observation, interviews, and documentation. The results showed that: 1. SIMPATIKA data management in the DIKMAD area of DIY Ministry of Religion's regional office was by the central SIMPATIKA operator's procedures. Judging from how SIMPATIKA management starts from the format, data collection, and data presentation, SIMPATIKA can be used to make accurate decision-making. 2. Decision making related to Educators and Education Personnel in the DIKMAD sector is currently firm and committed to following the established system regulations because the basis for decision making is based on SIMPATIKA data analysis. 3. SIMPATIKA's strengths include: (a) Real-Time Online Transaction (2) Rule by System (3) Self-Service Technology And Paperless, while the weakness is that the Ministry of Religion does not have a SIMPATIKA patent, this is an obstacle for the Ministry of Religion in its development.